Улучшение однородности магнитного поля в рабочей области магнитоизмерительного стенда - Лупиков, Валерий Сергеевич; Крюкова, Наталья Валерьевна; Машнев, Анатолий Егорович; Петров, Сергей Васильевич; Пелевин, Дмитрий Евгеньевич; Шубцов, Вячеслав Евгеньевич (НТУ "ХПИ", 2005)
Приведены результаты экспериментальных исследований распределения магнитного поля в рабочей области магнитоизмерительного стенда Отделения магнетизма Института электродинамики НАН Украины. Даны рекомендации по повышению точности измерений постоянного магнитного поля на стенде.

Experimental researches of magnetic field distributing in the working volume of a magnetic measuring stand of the Magnetism Department of Electrodynamics Institute of National Academy of Science of Ukraine are resulted. Recommendations on increasing of measuring exactness on the stand are given for the permanent external magnetic field.
Improvement of a magnetic field homogeneity in the working volume of a magnetic measuring stand
Keywords: электрическое оборудование; внешнее магнитное поле; электромагниты; ферромагнитные стержни; магнетизм; working volume; magnetic measuring stand; measurement; external magnetic field; electrical equipment; space device